Regional labor markets and aging in Germany - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
This paper analyzes how the aging labor force aþects the unemployment rate at the regional level in Germany. A theoretical model of equilibrium unemployment with spatial labor market interactions is used to study the eþects of age-related changes in job creation and job destruction. Using data for 343 districts, we then examine empirically the consequences of an aging labor force for the local labor markets in Germany. We apply diþerent estimation techniques to a spatial and time dynamic panel data model. According to the estimates, aging causes an increase in job destruction. In addition, aging in the local labor market increases job creation, while the spatial aging eþect on job creation in the local district is negative.
Keywords: J64; J63; J23; J61; R12; J10; 330; Regional Unemployment; Vacancies and Separations; Job Creation; Regional Mobility; Spatial Interactions and Matching; Aging of the Labor Force; Regionaler Arbeitsmarkt; Alternde Bevölkerung; Regionale Arbeitslosigkeit; Regionale Arbeitsmobilität; Räumliche Interaktion